2016
DOI: 10.1001/jamacardio.2016.1585
|View full text |Cite
|
Sign up to set email alerts
|

Population Effect of Differences in Cholesterol Guidelines in Eastern Europe and the United States

Abstract: IMPORTANCE The American College of Cardiology/American Heart Association (ACC/AHA) guidelines for management of blood cholesterol and current European Society of Cardiology/European Atherosclerosis Society (ESC/EAS) guidelines differ in how they identify adults in need of statin therapy; furthermore, it is unclear how this difference translates into numbers and characteristics of patients recommended for treatment. OBJECTIVE To determine the impact of the ACC/AHA and ESC/EAS cholesterol guidelines when appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Finally, we chose to define hypercholesterolemia and achieving control based on the ATP III guidelines due to their frequent use in the literature. However, these are relatively conservative in comparison to some national guidelines, as is apparent when examining the markedly lower cascade performance when applying AHA/ACC guidelines (see S1C Fig) . The comparability of countries is generally limited by a lack of universally used guidelines, as different guidelines are applied across countries and clinical settings and may even include geographical parameters, as is the case in the European Society of Cardiology (ESC) and European Atherosclerosis Society (EAS) guidelines [59,60]. Despite this, such a comparison still offers important insights into national and global care gaps and can be used for identifying effective policy as well as serve as markers of progress in tackling the burden of hypercholesterolemia.…”
Section: Plos Medicinementioning
confidence: 99%
“…Finally, we chose to define hypercholesterolemia and achieving control based on the ATP III guidelines due to their frequent use in the literature. However, these are relatively conservative in comparison to some national guidelines, as is apparent when examining the markedly lower cascade performance when applying AHA/ACC guidelines (see S1C Fig) . The comparability of countries is generally limited by a lack of universally used guidelines, as different guidelines are applied across countries and clinical settings and may even include geographical parameters, as is the case in the European Society of Cardiology (ESC) and European Atherosclerosis Society (EAS) guidelines [59,60]. Despite this, such a comparison still offers important insights into national and global care gaps and can be used for identifying effective policy as well as serve as markers of progress in tackling the burden of hypercholesterolemia.…”
Section: Plos Medicinementioning
confidence: 99%
“…However, ESC/EAS guidelines acknowledge that different LDL‐C goals have not been examined in RCTs. When applied to nationwide national samples similar numbers of adults were found to qualify for statin therapy in the United States and Poland regardless of the guideline used . The concordance is not similar in all countries of Europe.…”
Section: Guideline Recommendationsmentioning
confidence: 92%
“…When applied to nationwide national samples similar numbers of adults were found to qualify for statin therapy in the United States and Poland regardless of the guideline used. 19 The concordance is not similar in all countries of Europe. A modeling study utilizing data from the Copenhagen General Population Study found that ACC/AHA guidelines would prevent an estimated 34% ASCVD events compared to 13% using ESC/EAS guidelines in the study population.…”
Section: Rationale For Statin Use In Diabetes Mellitus From Randomimentioning
confidence: 96%
“…The authors note that a number of substantive and detailed reviews have been published with regards to these guidelines (4)(5)(6). We do not intend to replicate these but rather focus on certain core issues that may be relevant to day-to-day clinical practice.…”
Section: Introductionmentioning
confidence: 99%